Linguistic States and Sub-Regionalism: A Case Study Of Vidarbha - Megha Devle (Nav Vishnu Publications, 2016)
This book analyses some pertinent issues of the Indian Politics with reference to regions and sub-regions for their demand of separate state from the existing parent states.